ARK721: Computer Aided Architectural Design II / Faculty of Architecture, Planning & Surveying - UiTM, Faculty of Architecture, Planning & Surveying (Universiti Teknologi MARA (UiTM), 2023)
In this subject students are introduced to Computer Aided Design (CAD) software as designing tool. The program will commence with basic introduction to two-dimensional drawing and proceed to a more complex three-dimensional design and rendering techniques. Assignments begin with simple graphic exercise and proceed to major projects. These assignments include drawing exercises of selected project using CAAD software.